Civil Organisations and Regional Identity in the South Hungarian Great Plain - Murányi, István; Péter, Judit; Szarvák, Tibor; Szoboszlai, Zsolt (Discussion Papers, 2012)
The practice of the South Great Hungarian Plain’s regional planning differs from other regions in two aspects. First, while in the majority of Hungarian regions concepts and programs are dominated by economic employment policy and infra¬structural development, on the other hand, in the South Plain besides economic development, employment policy, and infrastructural development, the region’s human resource development also claims to be equal - as it is layed down in documents under preparation concerning development plans of this region. Second, - as far as we know - there are no other operative programs that can be found in other regions of Hungary concerning the development of civil society. In the framework of the research, the authors examined the adult population’s local and regional identity in the region, mainly investigating sociological dimensions (interpreting the notion of the different areas e.g. region, micro region, dwelling, attachment to different areas, features of local patriotism, the scale of values in the surroundings, expectations of the EU) and also features of civil organisations in the region (basic features, function, resources, and support for regional development). The aim of this executive summary is to introduce the features of the South Great Plain’s identity and the position of civil society by a harmonizing (regarding the method and the contents) closing study.